Disease-Modifying Effect of HBS1L-MYB in HbE/β-Thalassemia Patients in Bangladeshi Population - Jannatul Ferdous; Marzia Tasnim; Firdausi Qadri; Md. Ismail Hosen; Emran Kabir Chowdhury; Hossain Uddin Shekhar (Thalassemia Reports)
Background: Thalassemias are a group of autosomal recessive disorders and the most common inherited disease worldwide. Fetal hemoglobin (HbF) is the main oxygen carrier protein in the human fetus. Elevated HbF level is known to ameliorate the severity of HbE/β and β-thalassemia. This study aimed to investigate whether two commonly known HbF-associated SNPs (rs28384513 and rs4895441) in the HBS1L-MYB region are associated with HbF level and disease severity in Bangladeshi HbE/β-thalassemia patients. Methods: Blood samples were collected from 160 participants (120 HbE/β-thalassemia patients and 40 healthy controls). Hematological analysis was performed using complete blood count (CBC) and capillary Hb electrophoresis. After genomic DNA extraction, real-time PCR-based high-resolution melting (HRM) for SNP detection, targeting the HBS1L-MYB intergenic region, was done. Results: Patients carrying rs28384513 and rs4895441 SNPs had significantly higher HbF (1.29 ± 1.63 and 1.49 ± 1.7 g/dL, respectively) compared to major allele ‘TT’ and ‘AA’ (0.87 ± 1.1 and 1.19 ± 1.65 g/dL, respectively) with a p-value of 0.01 and 0.03, respectively. It has been detected that HbF levels in SNP-carrying patients significantly correlated with the higher transfusion interval (60 days, r = 0.38, p < 0.0001) and age of first transfusion (65 months, r = 0.26, p < 0.0028) in these patients. Further, non-transfusion-dependent patients had the highest HbF level (2.03 ± 2.05 g/dL) compared to transfusion-dependent moderate (0.58 ± 0.78 g/dL) and severe (0.84 ± 1.27 g/dL) patients generating a significant p-value < 0.0001 in One-Way ANOVA test. The minor allele frequencies of rs28384513 (G) and rs4895441 (G) were found to be 0.43 and 0.11 respectively. Conclusion: These findings suggest that SNPs of HBS1L-MYB may have a role in elevated HbF levels and ameliorating disease severity in terms of transfusion in HbE/β-thalassemia patients.